2014
DOI: 10.1016/j.jsat.2014.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum changes in methadone maintenance dose

Abstract: The optimal approach to postpartum dosing among women treated with methadone maintenance is unclear. We examined doses among 101 methadone-maintained pregnant women 2, 6 and 12 weeks postpartum, and compared the incidence of having doses held for oversedation during pregnancy and postpartum. The average dose at delivery was 83.3 mg, and the mean change from delivery to 12 weeks postpartum was −3.7 mg (95% CI −6.3, −1.1). The incidence of oversedation events per 10,000 days was 2.8 among pregnant women and 5.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Dividing the dose of methadone in half (split dosing) is an approved protocol for women in the third trimester of pregnancy because of the shorter half-life and larger clearances of medications during pregnancy (eg, Bogen et al, 2013 ). There is mixed evidence supporting the need to lower methadone or buprenorphine doses after delivery ( Jones et al, 2008a ; Bogen et al, 2013 ; Pace et al, 2014 ; Bastian et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Dividing the dose of methadone in half (split dosing) is an approved protocol for women in the third trimester of pregnancy because of the shorter half-life and larger clearances of medications during pregnancy (eg, Bogen et al, 2013 ). There is mixed evidence supporting the need to lower methadone or buprenorphine doses after delivery ( Jones et al, 2008a ; Bogen et al, 2013 ; Pace et al, 2014 ; Bastian et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…13 A larger study of 101 women found insignificant dose changes up to 3-month postpartum in 50% of women; the other 50% of women had either the same or higher doses postpartum. 14 The most provocative finding of our study is the lack of a postpartum decrease in methadone requirements up to 6-month postpartum. Recommendations from the Center for Substance Abuse Treatment, Medication-Assisted Treatment for Opioid Addiction in Opioid Treatment Programs, Treatment Improvement Protocol Series no.…”
Section: Discussionmentioning
confidence: 62%
“…11 Only recently have studies begun to build on this finding to assess the maternal impact of dose changes. [12][13][14] The objective of this study was to evaluate postpartum dose adjustments in women undergoing methadone for OUT during pregnancy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The postpartum period is a vulnerable period where overdose can pose significant risks to maternal and child health and wellbeing. This time can be particularly challenging for mothers with opioid use disorder (OUD), given high rates of postpartum depression, fragmented transitions of care from prenatal to postpartum providers, lapses in insurance following delivery, physiological changes impacting medication dose for treatment of OUD and the shame and stigma experienced by women secondary to neonatal opioid withdrawal or loss of child custody .…”
Section: Introductionmentioning
confidence: 99%